The Light of Alexandria in the Middle Ages, until its Collapse in the Mamluk Period - Altan Çetin; Alyaguot Yousif Hassan Ahmed (Şarkiyat Mecmuası)
The question that led to the research and writing of this article was created by the information that Ibn Battuta gave in his travel book about a lantern he saw when he set out on his travels but that was later destroyed. The scope of this article is about the history of the Lighthouse of Alexandria based on medieval Islamic period literature. More specifically, the main issue that determined the scope is to reveal what happened to the Lighthouse of Alexandria particularly the structural problems and repairs until its collapse in the Mamluk period. The study wanted to find out when and how this lighthouse was finally destroyed. This event took place in the Mamluks period and ultimately resulted in the disappearance of the lighthouse and the construction of a castle in the Qaitbay period. In this study, Islamic period sources, which provided information about the lighthouse from the 9th to the 15th centuries, were used. The method used to solve the determined problem was through evaluating and comparing historical literature. When and how was the Lighthouse of Alexandria destroyed during the Mamluk period? The lighthouse, one of the ancient wonders of the world, fell victim to the devastating earthquakes that Egypt was subjected to. In the period between 796-1480, Egypt was exposed to about 57 major and minor earthquakes, and about 22 of them affected the Lighthouse of Alexandria. Earthquakes of 796, 884, 956, 1303, 1334, 1341, 1348 caused the Alexandria Lighthouse to collapse. As we learned from historic records, Egyptian rulers had the lighthouse repaired at different times. For example, one of them was Mamluk Sultan Baibars. The historic literature revealed the fate of the Lighthouse of Alexandria occurred in 1375 when a severe earthquake caused it to collapse completely.